Efektivitas Implementasi Program One Day One Egg sebagai Upaya Pencegahan Kasus Stunting melalui Pemenuhan Gizi Ibu Hamil di Desa Grenden - Adhiansyah, Hanif Krisna; Arista, Jensi; Zulfa, Mayla Syifani; Farilla, Hilma; Wahyuni, Sri (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Stunting is a condition in which a child suffers from growth failure that is under the age of five or young that can be caused by chronic malnutrition and/or recurrent infection during the first thousand days of life. According to the Health Department of East Java Province data in 2018, Jember district is one of the districts in East Java that has the highest stunting cases of 39.2%.Stunting is a problem related to malnutrition.Stunting cases can occur from pregnancy to childhood. Stunting is one of the effects that can be caused by nutritional deficien.cies during the first thousand days of a child's life that can cause irreversible physical developmental disorders in a child, resulting in long-term and short-term effects. One solution that can be an attempt to prevent and reduce stunting cases is with a program to provide knowledge and attitude in nutritional fulfillment as well as health in pregnant mothers. The One Day One Egg activity is done by adjusting the posyandu schedule in the village of Grenden, Puger district, Jember. Stunting is caused by chronic malnutrition that occurs in the early stages of development, especially during the first 1,000 days of life, i.e. from pregnancy to the age of 2 years or 23 months.